Novel treatment for non-small cell lung cancer with brain metastases - Duyen, Le Nha; Dung, Ho Xuan (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Brain metastases is common in patients with non-small cell lung cancer (NSCLC) and it is associated with poorer prognosis. Several options to control the secondary brain tumors in the context include chemotherapy, whole-brain radiation, stereotactic surgery, surgery. However, chemotherapy is ineffective to those patients because of poor penetration through the blood-brain barrier. Whole-brain radiation therapy used to be a standard option for brain metastases. However, it potentially damages normal brain tissues and causes neurocognitive decline. Stereotactic radiotherapy has been considered in cases of three or fewer lesions, and the lesions less than 3 cm. In selective cases, surgical removal of brain metastases can be done. These local therapies were accompanied by systemic treatment due to spreading of the cancer. Recently, molecular targeted therapy has opened up a new era in cancer treatment, especially NSCLC with brain metastases. In this review, we discuss brain metastases occurring in NSCLC patients with driver gene mutations with some briefly demonstrated cases.